Media’s role, challenges, and ethics in journalism amid socio-political conflicts in contemporary society - Hassan, Joan T.; Baba, Dorcas; Ibrahim, Auwal Ahmed; Elisha, Jemimah Deynum (Yayasan Mitra Persada Nusantara, 2024)
- This study explores the intricate relationship between journalism and contemporary socio-political conflicts, focusing on the challenges journalists encounter when covering such issues. The study aims to analyze the ethical, physical, and economic difficulties faced by journalists, particularly in conflict-prone environments. It examines the role of journalism in shaping public discourse, the influence of political and economic interests on media narratives, and the rise of alternative news sources such as citizen journalism. Grounded in the theoretical framework of Peace Journalism, the study emphasizes ethical reporting practices that prioritize accuracy, fairness, and dialogue over sensationalism. A qualitative descriptive research method is employed, utilizing document analysis of scholarly literature, media reports, and relevant records to investigate media ethics and journalistic practices in multicultural Nigeria. The analysis highlights the complex interplay between media institutions, political forces, and public perception in conflict reporting. Findings reveal that journalists face significant risks, including threats to their physical safety, pressures from political and corporate entities, and ethical dilemmas in reporting sensitive issues. Additionally, social-political conflicts influence media polarization, alter news consumption patterns, and amplify the role of digital platforms in shaping public opinion. The study underscores the growing impact of citizen journalism, which challenges traditional media narratives but also raises concerns regarding misinformation. To address these challenges, the study proposes several recommendations, including strengthening press freedom, enhancing journalist training programs, enforcing ethical guidelines, promoting peace journalism initiatives, and fostering cross-border media collaboration. Furthermore, the study advocates for public awareness campaigns, investment in conflict reporting, and continuous research to monitor media trends. By implementing these measures, journalism can contribute more effectively to conflict resolution and democratic stability.